PKM DEVELOPMENT OF HOUSEHOLD BUSINESS AROMATHERAPY BRICKETS KHOLY ZAINI - Fithria, Abdi; Rahmadi, Adi; Sariana, Sariana; Rezekiah, Arfa Agustina (LPPM Univ. Ibn Khaldun Bogor, 2023)
People of Martapura City and its surroundings often use incense/bukhur as an air freshener for religious activities. One of the home businesses that produce it is Kholy Zaini. The business was founded 12 years ago with the premise that when pioneering it was that people in the city liked incense/bukhur, while most of it was obtained from imports from the island of Java. Even though it has been running for a long time until now there is still no IPRT and in its manufacture, I t still uses synthetic fragrances, which hurts health. This program is implemented to provide understanding and solutions to partners so that the products produced don’t negatively impact the future. The methods implemented include socialization activities, counseling, discussions, training, and mentoring. The solution that the PKM Team provides to partners is to replace synthetic fragrances with natural fragrances obtained from the distillation of ylang flowers. The process used to make incense/bukhur from natural fragrances is like making it in general, but the difference is da distillation of ylang flowers to get a natural fragrance. The PKM team succeeded in making a natural fragrance from the distillation of ylang flowers. In addition, the PKM team also teaches the company's bookkeeping to partners and develops a website to market their products. The advantages of this PKM activity are making incense/bukhur more environmentally friendly, partners can make the right decisions and increasing sal, es and making products known more widely.